Exploring patterns of technology use in UK college students: a cluster analysis of learners' digital practices. Issue 1 (2nd January 2019) - Sharpe, Rhona; Wu, Qi; Pavlakou, Metaxia
ABSTRACT: This study assesses the use of various technologies, from institutional virtual learning environments to Web 2.0 tools, amongst learners studying at six general Further Education colleges in the UK. The study surveyed 218 students from a range of disciplines and qualifications. Cluster analysis revealed distinct patterns of engagement with technologies in both personal/social and educational contexts. Some support was found for a connection between personal/social and academic uses of technology. In contrast to the dominant narrative of learners as digitally fluent technology users, the analysis showed the majority of learners were using educational technologies in fairly simplistic ways that satisfy the demands of their course. Significant relationships were found between digital practices in college and subject studied and gender. The discussion draws on the literature of digital literacy practices in order to interpret the findings and inform the planning and development of learning technologies.